Hypermetabolism and Substrate Utilization Rates in Pheochromocytoma and Functional Paraganglioma - Petrák, Ondřej; Haluzíková, Denisa; Klímová, Judita; Zítek, Matěj; Holaj, Robert; Michalský, David; Novák, Květoslav; Petráková-Doležalová, Radka; Kvasnička, Jan; Nguyen, Thi Minh Phuong Nikrýnová; Krátká, Zuzana; Matoulek, Martin; et al. (Biomedicines, 2022)
The overproduction of catecholamines in pheochromocytoma/paraganglioma (PPGL) induces a hypermetabolic state. The aim of this study was to evaluate the incidence of a hypermetabolic state and differences in substrate metabolism in consecutive PPGL patients divided by catecholamine phenotype. Resting energy expenditure (REE) and respiratory quotient (RQ) were measured in 108 consecutive PPGL patients and 70 controls by indirect calorimetry. Hypermetabolic state was defined according to the Mifflin St. Jeor Equation as a ratio above 110%. Hypermetabolic state was confirmed in 70% of PPGL patients, regardless of phenotype. Older age, prevalence of diabetes mellitus and arterial hypertension were correlated with hypermetabolic PPGL as compared to normometabolic form. Analysis according to overproduced catecholamine showed differences in VCO2 (p < 0.05) and RQ (p < 0.01) and thus different substate metabolism between phenotypes in hypermetabolic form of PPGL. Lipid utilization was higher in the adrenergic phenotype (p = 0.001) and positively associated with the percentage of REE ratio (R = 0.48, p < 0.001), whereas the noradrenergic phenotype preferentially oxidizes carbohydrates (P = 0.001) and is correlated with the percentage of REE ratio (R = 0.60, p < 0.001). Hypermetabolic state in PPGL is a common finding in both catecholamine phenotypes. Hypermetabolic PPGL patients are older and suffer more from diabetes mellitus and arterial hypertension. Under basal conditions, the noradrenergic type preferentially metabolizes carbohydrates, whereas the adrenergic phenotype preferentially metabolizes lipids.
Keywords: pheochromocytoma; substrate metabolism; respiratory quotient; metanephrines; catecholamines; indirect calorimetry; functional paraganglioma; resting energy expenditure